2013
DOI: 10.12691/ajbr-1-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Subcomponents of Vitamine B Complex Regulate the Growth and Development of Human Brain Derived Cells

Abstract: The work is focused on the role of single components of Vitamin B complex: pyridoxine, riboflavin, thiamine, and nicotinamide in the processes of growth and development of the human brain derived cells. We, also, have assayed the activity of Xanthine Oxidase in the presence of above mentioned subcomponents to delineate the possible mechanism of their action. Results indicate that the all components of Vitamin B complex might be responsible for cells' growth, maturation, proliferation. During early period of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Since mammals are not able to synthesize riboflavin, they must derive it from dietary sources. It has been reported that the addition of riboflavin to culture medium of human fetal brain cells including NSCs promotes cell growth and maturation . Taken together with our finding that S2101 represses hfNSC neurogenesis, this indicates that an adequate supply of riboflavin from mother to fetus is essential for LSD1 activation, and thus, for neurogenesis during brain development.…”
Section: Discussionsupporting
confidence: 81%
“…Since mammals are not able to synthesize riboflavin, they must derive it from dietary sources. It has been reported that the addition of riboflavin to culture medium of human fetal brain cells including NSCs promotes cell growth and maturation . Taken together with our finding that S2101 represses hfNSC neurogenesis, this indicates that an adequate supply of riboflavin from mother to fetus is essential for LSD1 activation, and thus, for neurogenesis during brain development.…”
Section: Discussionsupporting
confidence: 81%
“…The few nutritional studies that have investigated the association between vitamin B6 (pyridoxine) and SUA levels have not reported any association between vitamin B6 intake and the risk of hyperuricemia [13] or between the serum levels of vitamin B6 and those of UA [14]. However, the result shown in the example is consistent with experimental evidence showing that vitamin B6 greatly inhibits the activity of xanthine oxidase, the enzyme responsible for the last steps of the purine catabolism that promotes the formation of uric acid [15,16].…”
Section: Example: Serum Uric Acid (Sua) Levels As the Health Outcomesupporting
confidence: 62%
“…Moreover, coelomic fluid of earthworms, Eudrilus eugeniae [ 68 ] , Eisenia spp., [ 69 ] and Lumbricus spp. [ 70 ], are rich in riboflavin, which is essential for cellular proliferation [ 71 , 72 ], promotes the neural cell proliferation [ 73 ] and neural stem cell differentiation in cell culture, respectively [ 74 ]. Additionally, CF is used as a supplement in plant tissue culture [ 75 ].…”
Section: Efforts Made To Reduce or Replace Fbsmentioning
confidence: 99%